2022
DOI: 10.1038/s41522-022-00347-3
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous fungal biofilms: Conserved and unique aspects of extracellular matrix composition, mechanisms of drug resistance and regulatory networks in Aspergillus fumigatus

Abstract: The filamentous fungus Aspergillus fumigatus is an ubiquitous mold that can cause invasive pulmonary infections in immunocompromised patients. Within the lung, A. fumigatus forms biofilms that can enhance resistance to antifungals and immune defenses, highlighting the importance of defining the mechanisms underlying biofilm development and associated emergent properties. A. fumigatus biofilms display a morphology and architecture that is distinct from bacterial and yeast biofilms. Moreover, A. fumigatus biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 108 publications
(154 reference statements)
0
12
0
1
Order By: Relevance
“…11 In vitro, A. fumigatus was shown to form highly structured biofilms on both biotic and abiotic surfaces. 12 The presence of biofilms has been demonstrated in various Aspergillus diseases such as in people with cystic fibrosis (CF) and those with acute IPA. 13,14 Laboratory studies indicate that the MIC required to kill or inhibit biofilm structures of A. fumigatus are much higher than those required to kill/inhibit planktonic forms.…”
Section: In Vitro Susceptibility Testing and Treatment Failurementioning
confidence: 99%
See 1 more Smart Citation
“…11 In vitro, A. fumigatus was shown to form highly structured biofilms on both biotic and abiotic surfaces. 12 The presence of biofilms has been demonstrated in various Aspergillus diseases such as in people with cystic fibrosis (CF) and those with acute IPA. 13,14 Laboratory studies indicate that the MIC required to kill or inhibit biofilm structures of A. fumigatus are much higher than those required to kill/inhibit planktonic forms.…”
Section: In Vitro Susceptibility Testing and Treatment Failurementioning
confidence: 99%
“…13,14 Laboratory studies indicate that the MIC required to kill or inhibit biofilm structures of A. fumigatus are much higher than those required to kill/inhibit planktonic forms. 12,15 One study indicated that the fungus became increasingly resistant to polyenes, azoles, and echinocandins throughout its morphological differentiation to a mature biofilm phenotype. 12,15 Biofilm formation may reduce the activity of antifungal agents compared to planktonic cells.…”
Section: In Vitro Susceptibility Testing and Treatment Failurementioning
confidence: 99%
“…GAG is a cationic linear heteropolymer composed of α‐1,4‐linked galactose, N ‐acetylgalactosamine (GalNAc), and galactosamine (GalN) (Fontaine et al, 2011; Speth et al, 2019). As GAG is found on the surface of A. fumigatus hyphae and secreted as component of the extracellular matrix (ECM) of biofilms, it has multiple effects on host immune responses and biofilm formation (Liu et al, 2022; Speth et al, 2019). Interestingly, GAG was found only on the surface of hyphae and was absent in conidia (Briard et al, 2016; Fontaine et al, 2011; Loussert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently it was confirmed that filamentous fungi such as A. fumigatus , Aspergillus spp., F. graminearum , F. solani , F. oxysporum , Fusarium spp., Botrytis spp., and Verticillium spp. [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] form biofilms. Despite these studies, mixed polymicrobial biofilms of a filamentous fungus and a bacterium on the ocular surface have been rarely studied.…”
Section: Introductionmentioning
confidence: 99%